Pablo Gutiérrez's Expressionist Realism: Los libros repentinos, a Social Novel Between Testimony and Avant-Garde (XXI Century. Spanish Literature and Culture, 2024)
This article conducts an analysis of Los libros repentinos (2015), a novel by Pablo Gutiérrez that is grounded in two main axes: space and language. The first connects it to the neighborhood novel and the tradition of realist literature. On the other hand, the use of intertextuality and linguistic resources aligns it with avant-garde formalism. We argue that the Quixotism of the novel relies on dialogism to bridge these two concerns. In this way, Gutiérrez represents and advocates for a new way of writing social novels that is innovative in its aesthetics and committed in its themes.
Keywords: Commitment; testimony; social novel; quixotism; intertextuality